1992
DOI: 10.1126/science.1546315
|View full text |Cite
|
Sign up to set email alerts
|

A Human Gene Responsible for Zellweger Syndrome That Affects Peroxisome Assembly

Abstract: The primary defect arising from Zellweger syndrome appears to be linked to impaired assembly of peroxisomes. A human complementary DNA has been cloned that complements the disease's symptoms (including defective peroxisome assembly) in fibroblasts from a patient with Zellweger syndrome. The cause of the syndrome in this patient was a point mutation that resulted in the premature termination of peroxisome assembly factor-1. The homozygous patient apparently inherited the mutation from her parents, each of whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
184
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 351 publications
(195 citation statements)
references
References 12 publications
6
184
0
2
Order By: Relevance
“…HEK293 cells (41) and fibroblasts from a normal control and PBD patients defective in PEX12 (42), PEX10 (43), PEX2 (44), PEX1 (45), PEX6 (46), and PEX16 (47) were cultured as described.…”
Section: Methodsmentioning
confidence: 99%
“…HEK293 cells (41) and fibroblasts from a normal control and PBD patients defective in PEX12 (42), PEX10 (43), PEX2 (44), PEX1 (45), PEX6 (46), and PEX16 (47) were cultured as described.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescent microscopy of human fibroblasts was previously described (18). Human fibroblasts used in this study were from a normal, peroxisomal D-bifunctional protein deficiency patient (19) and a Zellweger syndrome patient (20).…”
Section: Methodsmentioning
confidence: 99%
“…Complementation studies have shown the involvement of at least 9 different genes, each associated with impaired biogenesis of peroxisomes when mutated (Shimozawa et al 1993;Moser et al 1995). Only a few of these genes have been truly identified (Shimozawa et al 1992;Dodt et al 1995).…”
mentioning
confidence: 99%